Enzyme blood level disorder as a marker of metabolic processes severity in multiple sclerosis - Markovska, Olena (My University, 2014)
Dynamics of membrane-bound enzymes activity changes in the blood of 67 patients with multiple sclerosis was investigated depending on the variety and duration of the disease.
Keywords: multiple sclerosis; enzymes